Peningkatan Pemahaman Etika Profesi sebagai Bekal Memasuki Dunia Kerja pada Siswa Lembaga Pelatihan Kerja (LPK) Mitra Sauri - Micael Jeriko Damanik; Maltus Hutagalung; Marihot Simanjuntak; Fransiska Tiurma Damanik4; Parlindungan Purba; Asrimen Zendrato; Dirwan Manik (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
The increasingly competitive world of work demands that workers possess not only technical competence but also a sound understanding of professional ethics. Students at the Mitra Sauri Job Training Institute (LPK), as prospective workers, need to be equipped with professional ethical values to enable them to behave professionally, responsibly, and with integrity in the workplace. This Community Service activity aims to improve students' understanding of professional ethics as a preparation for entering the workforce. The activity implementation method includes counseling, interactive lectures, discussions, and case studies related to the application of professional ethics in the workplace. The material presented includes the definition of professional ethics, professional attitudes and behavior, work discipline, responsibility, and communication ethics in the workplace. Evaluation of the activity was carried out through questions and answers and measuring participants' understanding before and after the activity. The results of the activity showed an increase in students' understanding of the importance of professional ethics and their awareness to apply it in the workplace. It is hoped that this activity can contribute to developing human resources who are work-ready, professional, and ethical.